Pengaruh Kekurangan Energi Kronis (Kek) Dengan Kejadian Anemia Pada Ibu Hamil Di Desa Tumpak Pelem Kecamatan Sawoo Kabupaten Ponorogo - Catur Wulandari (Jurnal Delima Harapan, 2017)
Anemia in pregnancy is also associated with increased maternal morbidity.According to WHO about 40% of maternal deaths in developing countries are associatedwith anemia in pregnancy and most anemia in pregnancy is caused by acute bleeding andpoor nutritional status. Based on the data of Ponorogo District Health Office 2015recorded 6,652 pregnant women, with the incidence of KEK as much as 21.19% andanemia as much as 5.86%. This study aims to determine the effect of chronic energydeficiency on anemia in pregnant women Tumpak Pelem Village, Sawoo District,Ponorogo Regency.The type of research used is observational research with cross sectional design.Sampling technique with probability sampling with 31 respondents.The result of statistical test obtained p value = 0.0002 (p≤0.05), which means thereis Influence of Chronic Energy Deficiency (KEK) to pregnancy anemia in pregnantwoman in Tumpak Pelem Village, Sawoo Sub-district, Regency of Ponorogo Year 2017.